2007
DOI: 10.1016/j.febslet.2007.10.048
|View full text |Cite
|
Sign up to set email alerts
|

Structural basis of mercury‐ and zinc‐conjugated complexes as SARS‐CoV 3C‐like protease inhibitors

Abstract: Five active metal-conjugated inhibitors (PMA, TDT, EPDTC, JMF1586 and JMF1600) bound with the 3C-like protease of severe acute respiratory syndrome (SARS)-associated coronavirus were analyzed crystallographically. The complex structures reveal two major inhibition modes: Hg 2+ -PMA is coordinated to C 44 , M 49 and Y 54 with a square planar geometry at the S3 pocket, whereas each Zn 2+ of the four zinc-inhibitors is tetrahedrally coordinated to the H 41 -C 145 catalytic dyad. For anti-SARS drug design, this Zn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
58
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(60 citation statements)
references
References 26 publications
1
58
0
1
Order By: Relevance
“…These include competitive inhibitors phenyl mercuric acetate (168, K i = 0.7 μM), thimerosal (169, K i = 2.4 μM), and phenyl mercuric nitrate (170, K i = 0.3 μM) ( Figure 33). 121,122 However, inhibition was more pronounced using zinc-conjugated compounds (171−174), i.e., 1-hydroxypyridine-2-thione zinc (171, K i = 0.17 μM) compared to Zn 2+ ions alone (K i = 1.1 μM). The X-ray crystal structure of SARS-CoV 3CL pro −168 (PDB ID 1Z1I) revealed that phenyl-bound mercury occupied the S3 pocket, which is responsible for its enzymatic activity.…”
Section: Journal Of Medicinal Chemistrymentioning
confidence: 99%
“…These include competitive inhibitors phenyl mercuric acetate (168, K i = 0.7 μM), thimerosal (169, K i = 2.4 μM), and phenyl mercuric nitrate (170, K i = 0.3 μM) ( Figure 33). 121,122 However, inhibition was more pronounced using zinc-conjugated compounds (171−174), i.e., 1-hydroxypyridine-2-thione zinc (171, K i = 0.17 μM) compared to Zn 2+ ions alone (K i = 1.1 μM). The X-ray crystal structure of SARS-CoV 3CL pro −168 (PDB ID 1Z1I) revealed that phenyl-bound mercury occupied the S3 pocket, which is responsible for its enzymatic activity.…”
Section: Journal Of Medicinal Chemistrymentioning
confidence: 99%
“…To date, several crystal structures of CoV M pro and the complex of M pro -inhibitor have been determined (7)(8)(9)(10)(11)(12)(13)(14)(15)(16). However, the 3-dimensional structure of FIPV M pro is still unavailable, deterring rational drug design against FIP.…”
mentioning
confidence: 99%
“…Many excellent and exhaustive studies have based this mechanism of catalysis and the structure of the catalytic site architecture to design several different classes of peptidomimetic inhibitors targeted against M pro of coronaviruses (including SARS) and other pathogenic viruses. Several M pro inhibitors have also been structurally characterized (Akaji et al, 2011;Bacha et al, 2008;Chu et al, 2006;Chuck et al, 2013;Grum-Tokars et al, 2008;Lee et al, 2007;Lee et al, 2009;Lee et al, 2005;Shan and Xu, 2005;Shao et al, 2007;Turlington et al, 2013;Verschueren et al, 2008;Wei et al, 2006;Yang et al, 2006;Yang et al, 2003;Yang et al, 2007;Zhang et al, 2010;Zhu et al, 2011).…”
Section: Functionmentioning
confidence: 99%